Damage and economic impact of wood-borers (Bivalvia, Teredinidae) on artisanal fishing in Morocco: a case study - EL JAMAAI, JAZILA; TAHERI, AHMED; EL AJJOURI, BILAL; ADLAN MERINI, MOHAMMED SAID; BORGES, LUÍSA M. S. (Mediterranean Marine Science, 2025)
This study presents the first comprehensive assessment of the economic impact of wood-boring bivalves from the family Teredinidae on artisanal fishing in Tangier, Morocco, following the establishment of a new fishing port that has seen a marked increase in infestations since its opening in 2018. We conducted a questionnaire survey with over 40 artisanal shipowners to evaluate the extent of damage and repair costs associated with teredinids. The results indicated that 77.5% of the fleet was affected, with a significant proportion reporting moderate damage. Analysis of wood samples revealed two dominant teredinid species: Lyrodus cf. pedicellatus, and Teredo bartschi, both recorded for the first time in Morocco, marking them as alien invasive species in the region. The vulnerability of wooden boats, particularly those constructed from softwoods (e.g., Picea sp. and Pinus sp.), was evident, while polyester boats remained unaffected. Annual repair costs due to shipworm damage were estimated to exceed Moroccan Dirham (MAD) 4.7 million (US$ 470,000), representing over 6% of the artisanal fishery annual value, significantly impacting the livelihoods of artisanal fishermen. Shipping activities through the Strait of Gibraltar likely facilitated the introduction of teredinids. Their adaptability and rising sea temperatures suggest teredinids’ range will continue to expand, threatening local fishing infrastructure. The findings underscore the urgent need for targeted management strategies to mitigate the economic and ecological impacts of these invasive species on artisanal fishing communities.